Feeding by Calanus glacialis in a high arctic fjord: potential seasonal importance of alternative prey. (25th July 2017) - Cleary, Alison C.; Søreide, Janne E.; Freese, Daniela; Niehoff, Barbara; Gabrielsen, Tove M.
Abstract: The copepod species Calanus glacialis is an important component of arctic marine food webs, where it is the numerically dominant zooplankton grazer and serves as a major prey item for fish, seabirds, and other predators. These copepods are typically considered to be phytoplanktivorous, although they are also known to feed on microzooplankton, and little is known about their diet in fall and winter. To investigate their feeding, C. glacialis gut contents were analyzed over an annual cycle in a seasonally ice covered arctic fjord using next generation sequencing of 18S rDNA. During the spring bloom, diatoms, particularly Thalassiosira spp., were important contributors to the dietary sequence reads. In addition to diatoms, Chytridiomycetes, fungal parasites of diatoms, also made up a large proportion of dietary sequence reads during this productive season. This provides one of the first indications of the potential importance of the mycoloop in marine environments. Just prior to the spring bloom, chaetognath sequences dominated the prey sequence reads from C. glacialis, suggesting potential predation on eggs or other early life stages of chaetognaths by C. glacialis . Other indications of omnivorous feeding outside of the spring bloom period included sequence reads from polychaetes in summer, at the time of peak polychaete larval abundance, and from Metridia spp. (Copepoda) in winter in prey sequences from C. glacialis . Incorporating such predation into our knowledge of Calanus spp. behaviour may help refine our understanding of Calanus spp. ecology, and potential responses of C. glacialis to ongoing climate change.